2004
DOI: 10.1590/s0100-46702004000200008
|View full text |Cite
|
Sign up to set email alerts
|

Application of differential scanning calorimetry in hair samples as a possible tool in Forensic Science

Abstract: The Differential Scanning Calorimetry (DSC) was used to study the thermal behavior of hair samples and to verify the possibility of identifying an individual based on DSC curves from a data bank. Hair samples of students and officials from Instituto de Química de Araraquara, UNESP were obtained to build up a data bank. Thus to sought an individual, under incognito participant of this data bank, was identified using DSC curves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…O pêlo é constituído por três camadas sobrepostas, sendo cutícula a superfície externa, formada por escamas queratinizadas e transparentes, córtex que é a camada intermediária formada por células queratinizadas homogêneas e a medula que corresponde à parte central composta por células mortas de várias formas e arranjos com presença ou não de bolhas de ar entre elas [3], [5], [7], [8], [9], [10]. A sua coloração é uma resposta ao tipo e à concentração de melanina em sua formação que, em maior quantidade, proporciona o seu escurecimento e na sua ausência, o clareamento [11], [12].…”
Section: Introductionunclassified
“…O pêlo é constituído por três camadas sobrepostas, sendo cutícula a superfície externa, formada por escamas queratinizadas e transparentes, córtex que é a camada intermediária formada por células queratinizadas homogêneas e a medula que corresponde à parte central composta por células mortas de várias formas e arranjos com presença ou não de bolhas de ar entre elas [3], [5], [7], [8], [9], [10]. A sua coloração é uma resposta ao tipo e à concentração de melanina em sua formação que, em maior quantidade, proporciona o seu escurecimento e na sua ausência, o clareamento [11], [12].…”
Section: Introductionunclassified
“…Past research has, for example, screened the thermal behavior of hair retrieved from students and officials representing different ethnic groups using DSC, although at higher temperatures (up to 600 °C) than our study. The data showed that although hair DSC curves did not possess enough discriminative power for ethnic classification, the data did show unique characteristics linked to a specific individual [ 44 ]. Furthermore, other studies would include analysis of the thermal properties of the DSC plots, such as onset temperature, melting temperature, and melting enthalpy [ 40 , 41 ], although, in this study, we were not interested in quantitatively studying melting dynamics of alpha-keratin between different hairs for which DSC finds unique applications in cosmetic hair studies related to hair damage and repair.…”
Section: Resultsmentioning
confidence: 99%
“…The metal ions were also determined by complexometric tritrations with standard EDTA solution using xylenol orange, as indicator [10].…”
Section: Methodsmentioning
confidence: 99%